Murder nature weather and violent crime in Brazil - Phoebe W. Ishak (Freie Universität Berlin, School of Business & Economics, 2021)
This paper examines the effect of weather shocks on violent crime using disaggregated data from Brazilian municipalities over the period 1991-2015. I document that adverse weather shocks in the form of droughts lead to a significant increase in violent crime, with the effect appearing to persist beyond the growing season and over the medium run. To explain this persistence, I show that weather uctuations are positively associated not only with agriculture yields, but also with the overall economic activity. Moreover, evidence shows the dominance of opportunity cost mechanism re ected in the uctuations of the labor income especially for the agriculture and unskilled workers, giving credence that it is indeed the labor income that matters and not the general socio-economic conditions. Other factors such as local government budget capacity, (un)-employment, poverty, inequality, and psychological factors do not seem to explain violent crime rates.
urn:nbn:de:kobv:188-refubium-29265-0
Keywords: 330; Weather shocks; violent crime; labor market; Brazil